PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (STUDI EMPIRIS PERUSAHAAN PERDAGANGAN, JASA DAN INVESTASI TERDAFTAR DI BEI TAHUN 2015-2017) - Bestari, Fidia Damba; Satyawan, Made (Jurnal Akuntansi AKUNESA, 2020)
This study aims to provide empirical evidence related to the influence of the expertise of the audit committee, audit committee charter, audit committee size, and audit committee meetings on the timeliness of financial reporting on trade, service and investment sector companies listed on the Indonesia Stock Exchange (IDX) in 2015 until 2017. This study used a purposive sampling method, namely sampling based on certain criteria, obtained as many as 147 sample data that match the criteria. Research carried out using multiple linear regression data analysis techniques with SPSS 23 test equipment wich obtained the results of the research audit committee meeting variables has negatively effect the timeliness of financial reporting wich is in line with the result of research by Anugrah & Laksito (2017), while the variable expertise of the audit committee, audit committee charter and audit committee meetings have no effect.